KNOWLEDGE OF THE NURSING TEAM ON VENTILATOR-ASSOCIATED PNEUMONIA (VAP) PREVENTION STRATEGIES IN THE INTENSIVE CARE UNIT ULIN HOSPITAL BANJARMASIN - Trifianingsih, Dyah; Ivana, Theresia; Hawini, Zikarara (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2024)
Abstract The chronic disease that the use of a mechanical ventilator can cause is pneumonia. Using a ventilator for a long time in the ICU is at risk of developing a nosocomial infection called ventilator-associated pneumonia. However, bundle care prevention strategies have proven to be highly effective in reducing the incidence of VAP. One of the factors in nurses' running bundle care is knowledge of VAP prevention strategies. This research aimed to describe and analyze the nursing team's knowledge of ventilator-associated pneumonia prevention strategies. This type of research was quantitative research with a descriptive method. The sample of this study consisted of nurses in the ICU room of Ulin Hospital, Banjarmasin, and 73 people were selected using the Total Sampling technique. Data collection will be done using a questionnaire, data analysis, and frequency distribution. This study showed that the level of knowledge of ICU nurses at Ulin Hospital Banjarmasin regarding VAP prevention strategies was in a suitable category: 51 people (69.8%), moderate ten people (13.7%), and 12 people (16.5%) lacking. Nurses in the ICU room at Ulin Hospital, Banjarmasin, have varying levels of knowledge; namely, there is good knowledge, some are sufficient, and some are still lacking in understanding VAP prevention strategies. Keywords: Knowledge, VAP Bundle, Ventilator-Associated Pneumonia